Color Enhancement of Rambutan Peel Anthocyanins Extracts using Co-Pigmentation with Gallic Acid for pH-Sensitives Dye - Perdani, Arum Widyastuti; Setiowati, Arima Diah; Purwono, Bambang; Supriyadi, Supriyadi (Trends in Sciences, 2025)
Rambutan peels typically contain anthocyanins that can be utilized as pH-sensitive dye for intelligent food packaging. Therefore, this study aimed to isolate anthocyanins from rambutan peels and investigate their co-pigmentation with gallic acid (GA) to enhance color intensity while maintaining a pH sensitivity. Rambutan peel anthocyanins extracts (RPAE) were extracted using ultrasound-assisted extraction with 0.2 % citric acid in 96 % ethanol. The purification of RPAE was carried out using a chromatography column with Sephadex LH-20 as the stationary phase. Co-pigmentation was then performed using GA at various molar ratios of RPAE to GA (1:0, 1:100, 1:200, 1:300, 1:400 and 1:500). The results showed that the purification process with Sephadex LH-20 increased the anthocyanins content of RPAE to 157.50 mg CyE/100 g extract. After purification, RPAE was found to primarily consist of cyanidin 5-O-glucoside, delphinidin-3-O-glucoside, cyanidin 3-O-galactoside, delphinidin (aglycon), cyanidin-3-O-glucoside, pelargonidin 3-O-glucoside, and cyanidin (aglycon). Co-pigmentation with GA significantly reduced the degradation of total anthocyanin content compared to native RPAE during the 7-day observation period. Additionally, co-pigmentation with GA enhanced color intensity, as demonstrated by a decrease in the L* value across pH 1-10, an increase in the a* and b* values at low pH, and a decrease in the a* and b* values at high pH. However, compared to non-co-pigmentation, co-pigmentation with GA exhibited more pronounced color differences across varying pH levels, marked by higher a* at low pH and lower b* and L* at high pH. The interaction between GA and RPAE, presumably via hydrogen bonding comprising the carbonyl group of RPAE and GA, produced hyperchromic and bathochromic effects. These findings indicate that co-pigmentation with GA enhances the pH sensitivity of RPAE, making it a promising candidate for developing intelligent food packaging systems that can visually indicate changes in pH, such as monitoring food spoilage or freshness. HIGHLIGHTS The purification of rambutan peel anthocyanins extracts using Sephadex LH-20 increased the yield to 157.50 mg CyE/100 g extract, identifying cyanidin, delphinidin, and pelargonidin derivatives. Co-pigmentation of rambutan peel anthocyanins extracts with gallic acid reduced the degradation of total anthocyanins, increased color intensity, and maintained pH sensitivity. The co-pigmentation mechanism of rambutan peel anthocyanin extracts with gallic acid involved molecular interactions with the carbonyl group of anthocyanins. GRAPHICAL ABSTRACT